Elucidating the effect of nitrogen occupancy on the hydrogen evolution reaction for a series of titanium oxynitride electrocatalysts - Yang,G; Zhou,Y; Wang,M; Murawski,J; Oldham,L; Tian,T; Stephens,IEL; Kafizas,A (ChemCatChem, 2023)
Titanium nitride (TiN) shows desirable properties for use as an electrocatalyst and catalyst support, as it possesses high electrical conductivity and excellent corrosion resistance. Any oxygen and humidity present or incomplete nitridation during the synthesis process of nitrides can lead to an increasing oxygen content. However, the role of oxygen contents or nitrogen occupancies in the bulk of the nitrides during the electrocatalytic reactions is not well understood. In this work, we have synthesised a series of titanium oxynitrides with varied bulk nitrogen occupancies by ammonolysis at different temperatures. Higher ammonolysis temperatures will give a higher nitrogen occupancy but result in a lower surface area. The geometric activities towards the hydrogen evolution reaction (HER) have been normalised by the electrochemically active surface areas (ECSA) and the BET surface areas to get the specific activities. Their specific activity towards the HER is found to be strongly correlated with the bulk nitrogen occupancy and a higher bulk nitrogen occupancy is beneficial to the specific HER activities.